A survey of students’ perception of the role and image of school librarians in Ibadan south west local government area of Oyo state (2012)
This paper investigates perception of students of the role and image of the school/teacher librarian in selected secondary schools in Ibadan South West Local Government Area of Oyo State. The study adopted descriptive survey research design. Stratified random sampling technique was used to select 10 schools from 25 public secondary schools in Ibadan South -West Local Government Area of Oyo State. Two hundred students in the selected schools constituted the sample of the study. Data was collect cd using a validated questionnaire tagged 'Perception of Librarian's Role and Image1 Two research questions and three null hypotheses were tested at 0.05 level of significance. The data were analysed using simple percentages and students T- Test statistics. The findings show that students have good perception of the role and image of the school librarian. There was no significant difference between male and female students' perception of the role of the librarian. There was a significant difference between the perception of students in arts and Science class. It is recommended that 'Information literacy skills instruction Programme should be integrated into the school Curriculum and library hour on the school time-table.